2000
DOI: 10.1021/jo991399g
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Derived 3‘-(Carboxymethyl)-3‘-deoxyribonucleosides and 2‘,3‘-Lactones as Synthetic Precursors for Amide-Linked Oligonucleotide Analogues1

Abstract: Treatment of a 1,2-O-isopropylidene-3-ketopentofuranose derivative (obtained from D-glucose) with [(ethoxycarbonyl)methylene]triphenylphosphorane and catalytic hydrogenation of the resulting alkene gave stereodefined access to 3-(carboxymethyl)-3-deoxy-D-ribofuranose derivatives. Esters of 5-O-acetyl- or 5-azido-5-deoxy-3-(carboxymethyl)-D-ribofuranose were coupled with nucleobases to give branched-chain nucleoside derivatives. Ester saponification and protecting group manipulation provided 2'-O-(tert-butyldim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…Due to small difference of the Rf values of 27 and 28, their separation was successful at small scale only (ca 2 g of mixture per run). The 1,2;5,6-di-O-isopropylidene-α-L-glucofuranose 27 was then subjected to the oxidation/reduction (a. CrO3-Py-Ac2O; 34 b. NaBH4) sequence to invert the configuration at the C3 position to produce the L-allose 29 which in turn was subjected to dehomologation (a. H5IO6, b. NaBH4 36,37 ) at a 1 g scale which furnished the 1,2-O-isopropylidene-α-L-ribofuranose 32 in a cumulative 69% yield (29→ 32). As mentioned above for the D-enantiomer this process did not function well at elevated scale.…”
Section: 62mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to small difference of the Rf values of 27 and 28, their separation was successful at small scale only (ca 2 g of mixture per run). The 1,2;5,6-di-O-isopropylidene-α-L-glucofuranose 27 was then subjected to the oxidation/reduction (a. CrO3-Py-Ac2O; 34 b. NaBH4) sequence to invert the configuration at the C3 position to produce the L-allose 29 which in turn was subjected to dehomologation (a. H5IO6, b. NaBH4 36,37 ) at a 1 g scale which furnished the 1,2-O-isopropylidene-α-L-ribofuranose 32 in a cumulative 69% yield (29→ 32). As mentioned above for the D-enantiomer this process did not function well at elevated scale.…”
Section: 62mentioning
confidence: 99%
“…a transformation of the D-allose (a hexose) to D-ribose (a pentose) can be performed using orthoperiodic acid H5IO6 followed by NaBH4 reduction. 36,37 The orthoperiodic acid is strong enough (pKa ca 3.3 38 ) to promote a hydrolysis of the more reactive C5-C6 acetonide in 9 to liberate a diol 10 which was subsequently cleaved by the same reagent to furnish the aldehyde 11 which in turn was subjected to NaBH4 reduction to yield the ribo compound 12. This procedure is very attractive and in fact it was successfully used on a small scale (1 g) in good yields (e.g.…”
mentioning
confidence: 99%
“…Although the syntheses that start from nucleosides are relatively straightforward, the need for separate modification of each of the four natural nucleosides makes the overall approach laborious. Robins, Peterson and co-workers [113] developed a more convergent route that uses a common carbohydrate precursor, prepared from D -xylose, to access all four modified nucleosides (Fig. 17, Route 1).…”
Section: Synthesis 3'-ch 2 -Co-nh-5' (Type Am1) Amide Linkagesmentioning
confidence: 99%
“…Robins and co-workers have also developed synthesis of 1 starting from d -glycose or d -xylose. 6 The sugar route diverges at the common intermediate 2 (Figure 1) on which the desired heterocylces can be installed in a straightforward manner. However, we found that Robin’s route from sugars was complicated at the finals steps by the need to cleave the ester (see 2 ) and, consequently, laborious reintroduction of 2’-OH and heterocycle protecting groups, which being base labile, were lost during the ester cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we report optimization of our synthetic route7 by adopting the initial steps from the Robin’s synthesis to prepare the key intermediate 3 starting from d -xylose 6. The key features that ensure efficiency of the new route are chemoselective reduction of the ester and minimization of protecting group manipulation.…”
Section: Introductionmentioning
confidence: 99%